2019
DOI: 10.1016/j.tine.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling predictors of UK undergraduates’ attitudes towards smart drugs

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
5
18
0
3
Order By: Relevance
“…For instance, some studies separate marijuana or cannabis use from each other IDU [ 65 , 69 ]. Others refer to a mesh of terms e.g., neuroenhancing substances (could include coffee, energy drinks, nicotine, alcohol) or psycostimulants [ 70 ]; illicit stimulants (amphetamines, Fenethylline, Ritalin, Concerta, Dexedrine, Adderall, Vyvanse) [ 71 ]; nonmedical attention deficit hyperactivity disorder (ADHD) medication [ 72 ]; illicit substances (including cocaine, designer drugs, and nonmedical use of prescription stimulants and opioids) [ 73 ]; illicit drug use, and misuse of prescription stimulants, sedatives, and opioids [ 74 ]; hallucinogen use [ 75 ]; smart drugs (aka cognitive enhancers, prescription drugs taken, either without a prescription or at a dose exceeding that which is prescribed) [ 76 , 77 ]; street drugs vs. prescription drugs [ 78 ]; or nonmedical use of prescription stimulants [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies separate marijuana or cannabis use from each other IDU [ 65 , 69 ]. Others refer to a mesh of terms e.g., neuroenhancing substances (could include coffee, energy drinks, nicotine, alcohol) or psycostimulants [ 70 ]; illicit stimulants (amphetamines, Fenethylline, Ritalin, Concerta, Dexedrine, Adderall, Vyvanse) [ 71 ]; nonmedical attention deficit hyperactivity disorder (ADHD) medication [ 72 ]; illicit substances (including cocaine, designer drugs, and nonmedical use of prescription stimulants and opioids) [ 73 ]; illicit drug use, and misuse of prescription stimulants, sedatives, and opioids [ 74 ]; hallucinogen use [ 75 ]; smart drugs (aka cognitive enhancers, prescription drugs taken, either without a prescription or at a dose exceeding that which is prescribed) [ 76 , 77 ]; street drugs vs. prescription drugs [ 78 ]; or nonmedical use of prescription stimulants [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…One population for whom use of CE is thought to be particularly prevalent is university students, who seek to enhance functioning to improve academic performance [2,[6][7][8]. The reported prevalence of CE use among students varies markedly, ranging from 5-35% in US studies [8], 1-16% in Continental Europe [9][10][11], and 9-17% in studies of UK students [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps unsurprisingly, studies have found users to be less concerned about the safety of CE than non-users [4,20], and perceptions of the severity of possible health risks have been inversely associated with willingness to use CE [21][22][23][24][25][26][27]. We recently demonstrated that perceived harmlessness and the belief that an individual knows enough about CE to use them safely were significant positive predictors of attitudes towards CE, which in turn predicted CE use in UK university students [12]. However, to date, no study has examined where users and non-users obtain safety information, or the accuracy of their knowledge of drug safety.…”
Section: Introductionmentioning
confidence: 99%
“…The normative changes taking place in the modern world concerning narcotic drugs, the creation of a positive image of them in numerous media, and at the same time, the weakening of the role of the family and secularization processes have been recognized as crucial determinants of the changes in attitudes towards psychoactive drugs observed today [ 6 , 35 , 36 , 37 ]. Reaching for drugs with psychoactive properties may also be conditioned by the attitudes towards such drugs acquired from the external environment; for example, the perception of drugs as safe, intelligence-enhancing, and at the same time, accessible [ 38 ].…”
Section: Mass Culture and Its Impactmentioning
confidence: 99%